Experimental correlations between aerodynamics, wall-pressure fluctuations, and noise transmission through a window downstream of a step in a flow. (1st January 2014) - Bessis, R.; Brizzi, L-E.; Gervais, Y.
We investigate the effects of vortex dynamics and unsteady flow separation downstream of a forward facing step on the inside noise radiation through a glass window in a low-speed turbulent flow. Investigations have been performed in an anechoic wind tunnel and include simultaneous measurements between wall and acoustic pressures and the velocity field. The objective is to identify the aerodynamic sources and analyse the link between turbulence and acoustic emission. Spectral and coherence analysis of the fluctuating pressures are used to characterise the temporal scale of the unsteady aerodynamics. Spatial correlation applied to synchronous wall-pressure/velocity measurements successfully catches hydrodynamic excitation mechanism and highlights the strong contribution of vortex shedding to the wall pressure fluctuations. As an attempt to link aerodynamics and acoustic emission, correlation analysis is also applied to acoustic pressure signals with more mixed results. This might be explained by a loss of spatial information in the acoustic measurement.